Experiences and views of people who frequently call emergency ambulance services: A qualitative study of UK service users - Bridie A. Evans; Ashra Khanom; Adrian Edwards; Bethan Edwards; Angela Farr; Theresa Foster; Rachael Fothergill; Penny Gripper; Imogen Gunson; Alison Porter; Nigel Rees; Jason Scott; et al. (Health Expectations)
Abstract Introduction People who call emergency ambulances frequently are often vulnerable because of health and social circumstances, have unresolved problems or cannot access appropriate care. They have higher mortality rates. Case management by interdisciplinary teams can help reduce demand for emergency services and is available in some UK regions. We report results of interviews with people who use emergency ambulance services frequently to understand their experiences of calling and receiving treatment. Methods We used a two‐stage recruitment process. A UK ambulance service identified six people who were known to them as frequently calling emergency services. Through third‐sector organisations, we also recruited nine individuals with healthcare experiences reflecting the characteristics of people who call frequently. We gained informed consent to record and transcribe all telephone interviews. We used thematic analysis to explore the results. Results People said they make frequent calls to emergency ambulance services as a last resort when they perceive their care needs are urgent and other routes to help have failed. Those with the most complex health needs generally felt their immediate requirements were not resolved and underlying mental and physical problems led them to call again. A third of respondents were also attended to by police and were arrested for behaviour associated with their health needs. Those callers receiving case management did not know they were selected for this. Some respondents were concerned that case management could label frequent callers as troublemakers. Conclusion People who make frequent calls to emergency ambulance services feel their health and care needs are urgent and ongoing. They cannot see alternative ways to receive help and resolve problems. Communication between health professionals and service users appears inadequate. More research is needed to understand service users' motivations and requirements to inform design and delivery of accessible and effective services. Patient or Public Contribution People with relevant experience were involved in developing, undertaking and disseminating this research. Two public contributors helped design and deliver the study, including developing and analysing service user interviews and drafting this paper. Eight public members of a Lived Experience Advisory Panel contributed at key stages of study design, interpretation and dissemination. Two more public contributors were members of an independent Study Steering Committee.